New tools for the systematic analysis and visualization of electronic excitations: II. Applications - Plasser, Felix; Mewes, Stefanie; Wormit, Michael; Dreuw, Andreas (The journal of chemical physics, 2014)
The excited states of a diverse set of molecules are examined using a collection of newly implemented analysis methods. These examples expose the particular power of three of these tools: (i) natural difference orbitals (the eigenvectors of the difference density matrix) for the description of orbital relaxation effects, (ii) analysis of the one-electron transition density matrix in terms of an electronhole picture to identify charge resonance and excitonic correlation effects, and (iii) state-averaged natural transition orbitals for a compact simultaneous representation of several states.
Gesehen am 11.12.2017